2018
DOI: 10.1152/ajpgi.00087.2018
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of ClC-2 reveals critical functions of adherens junctions in colonic homeostasis and tumorigenicity

Abstract: Adherens junctions (AJs), together with tight junctions (TJs), form an apical junctional complex that regulates intestinal epithelial cell-to-cell adherence and barrier homeostasis. Within the AJ, membrane-bound E-cadherin binds β-catenin, which functions as an essential intracellular signaling molecule. We have previously identified a novel protein in the region of the apical junction complex, chloride channel protein-2 (ClC-2), that we have used to study TJ regulation. In this study, we investigated the poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Additionally, in a Chloride channel protein-2 (CIC-2; CLCN2 ) null mouse model, recovery from DSS-induced colitis was impaired and the epithelial permeability was decreased [89]. Although these results were firstly attributed to compromised TJ function [89], it was subsequently shown that the AJs were also responsible [90]. E-cadherin and β-catenin distribution as well as the ultrastructural tissue morphology were specifically altered in the colon while it was retained in small intestine [90].…”
Section: E-cadherin In Inflammatory Bowel Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in a Chloride channel protein-2 (CIC-2; CLCN2 ) null mouse model, recovery from DSS-induced colitis was impaired and the epithelial permeability was decreased [89]. Although these results were firstly attributed to compromised TJ function [89], it was subsequently shown that the AJs were also responsible [90]. E-cadherin and β-catenin distribution as well as the ultrastructural tissue morphology were specifically altered in the colon while it was retained in small intestine [90].…”
Section: E-cadherin In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Although these results were firstly attributed to compromised TJ function [89], it was subsequently shown that the AJs were also responsible [90]. E-cadherin and β-catenin distribution as well as the ultrastructural tissue morphology were specifically altered in the colon while it was retained in small intestine [90]. These observations suggest that CIC-2 is associated with the AJs’ function specifically in the colon [90].…”
Section: E-cadherin In Inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the chloride channel ClCN2, also called ClC-2, in the regulation of tight junctions' composition in the small intestine has been recently uncovered (Nighot and Blikslager, 2012). As ClCN2 seemed to be an important actor of epithelial integrity and maintenance of the tight junctions, Jin et al questioned its involvement in adherens junctions (AJ) and its interaction with b-catenin (Jin et al, 2018). b-catenin binds E-cadherin in the adherens junctions.…”
Section: Clcn2mentioning
confidence: 99%
“…As ClCN2 seemed to be an important actor of epithelial integrity and maintenance of the tight junctions, Jin et al . questioned its involvement in adherens junctions (AJ) and its interaction with β-catenin ( Jin et al., 2018 ). β-catenin binds E-cadherin in the adherens junctions.…”
Section: Clcn2mentioning
confidence: 99%